Assessing Candidate Serum Biomarkers for Alzheimer’s Disease: A Longitudinal Study - Zabel, Matthew (2012)
Because of the growing impact of late onset cognitive loss, considerable effort has been directed toward the development of improved diagnostic techniques for Alzheimer’s disease (AD) that may pave the way for earlier (and more effective) therapeutic efforts. Serum-based biomarkers are the least expensive and invasive modality for screening and routine monitoring. We systematically reviewed the literature to assemble a list of serum biomarkers relevant to AD. In parallel, we conducted a proteomic LC-MS/MS analysis of serum collected from neurologically normal subjects and subjects with mild cognitive impairment (MCI) and early AD (n = 6 in all). Complement C3 and alpha-2-macroglobulin were identified from both the literature review and our proteomic screen for further validation. For these two candidates, ELISA was performed on serum collected from a small independent cohort of subjects for longitudinal analysis. Serum was serially collected from neurologically normal subjects (n = 5) and subjects with MCI who were subsequently followed for a period of two years (n = 5) and regrouped into stable MCI and progressive MCI or AD (n = 6). The ability of each marker to predict which subjects with MCI would progress to dementia and which would remain cognitively stable was assessed. Patients with probable cerebral amyloid angiopathy were also identified (n = 3). This preliminary analysis tested the most-promising serum protein biomarkers for AD and we concluded that none are yet ready for use in the clinical diagnosis and management of dementia. However, a more thorough assessment in longitudinal studies with higher statistical power is warranted.